Sel T Regulator CD4+CD25+ Mencegah Terjadinya Fenotip Letal pada Mencit Defisiensi CD122 - Rifa’i, Muhaimin; -, Widodo (Jurnal Veteriner; Vol 12, No 3 (2011))
Mice with a deficiency of cluster of differentiation/CD122 molecules experience increased memory Tcells. Increased memory T cells are activated and interfered with homeostasis that cause death at the ageof 10 ~ 12 weeks. To clarify whether the expression of CD25 molecules on CD4+ T cells responsible for thedevelopment of lethal phenotypes in CD122-/- mice, we did a transfusion of CD4+CD25+ T cells from normalmice to CD122-/- neonates. Transfusion of purified CD4+CD25+ T cells as much as 3 x 104 can prevent theoccurrence of lethal phenotypes generally experienced by CD122-/- mice. Transfusion of CD4+CD25+ T cellsin CD122-/- neonates cause all of the abnormalities that occur in T cell and leukocyte cells can be preventedand develop into normal. Similarly, the hematocrit that decreased dramatically in CD122-/- mice candevelop normally after receiving a transfusion of CD4+CD25+ T cells. In contras, transfusion of CD4+CD25-T cells in CD122-/- mice did not have the effect of preventing the development of the abnormalities inCD122-/- mice. CD4+CD25+ T cells that are lost in periphery of CD122-/- mice can restore to normal afterreceiving a transfusion of CD4+CD25+ T cells. These results clearly show that the expression of IL-2R?(CD25) on CD4+ T cells become pre-requisite for CD4 T cell population in order to play a role as regulatorcells.
Keywords: CD4+CD25+, sel T regulator, CD122-/-